2020
DOI: 10.1590/1519-6984.193974
|View full text |Cite
|
Sign up to set email alerts
|

Esculent coating of spider silk enhanced the preservation and shelf life of apricot

Abstract: Abstract According to the Food and Agriculture Organization (FAO), roughly one-third of the total food produced is lost globally. The major cause of this wastage is the perishability of fruits and vegetables. Therefore, researchers have endeavored to develop an effective preservation technique. Our study explored the potential application of spider silk as an odourless and edible preservative coating for fruits. The spider silk was collected from spiders reared in the laboratory, following by degumming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The antioxidant content of strawberries during storage decreased by compounds that antioxidants easily degraded by temperature, light and ambient air. In another study, coating raspberries with aloe vera gel could increase the resistance to spoilage by increasing the antioxidant capacity and antioxidant enzymes [24]. Other studies have also shown that the reduction in the antioxidant content [25].…”
Section: Total Antioxidants Of Coated Strawberriesmentioning
confidence: 92%
“…The antioxidant content of strawberries during storage decreased by compounds that antioxidants easily degraded by temperature, light and ambient air. In another study, coating raspberries with aloe vera gel could increase the resistance to spoilage by increasing the antioxidant capacity and antioxidant enzymes [24]. Other studies have also shown that the reduction in the antioxidant content [25].…”
Section: Total Antioxidants Of Coated Strawberriesmentioning
confidence: 92%
“…The edible coating may contain antimicrobial and antioxidant additives which can be formulated from a single gum, blends, or even multicomponent. Most of the edible coatings are directly applied onto the surfaces of fresh produce by dipping or spraying followed by air drying (Tahir et al, 2019). The application of edible coating on fresh produce provides a barrier against the movement of gas and moisture on their surface.…”
Section: Introductionmentioning
confidence: 99%